FROM POPULARITY TO ELECTABILITY: POLITICAL BRANDING OF CELEBRITY CANDIDATES IN THE 2024 BANDUNG REGENCY REGIONAL ELECTION - Ina Perdana Putri Prasetio; Astika Ummy Athahirah; Hasna Azmi Fadhilah (Fakultas Politik Pemerintahan, 2026)
The involvement of artists in local politics is growing in Indonesia, and popularity has become one of the most important capitals for gaining political support. This study aims to analyze the political branding built by candidates with artist backgrounds in the 2024 Bandung Regency Regional Head Election and explain their contribution to increasing electability. The research uses a Quasi-Qualitative Design (QQD) approach, with data collected through interviews, observations, documentation, and questionnaires. Data analysis was carried out using NVivo 12 with reference to Philbrick and Cleveland's political branding framework, which includes introspective evaluation, multi-stakeholder evaluation, brand mantra, offline footprint, online footprint, and integration. The results of the study show that political branding is built through candidate popularity, stakeholder support, political slogans, direct campaigns, and social media optimization. This strategy can foster a positive image and strengthen the candidate's relationship with the community. The study's findings also show that political branding increases electability by boosting voter liking, willingness to vote, intention to recommend candidates to others, and the intensity of public conversations about candidates. Although popularity as an artist is the starting capital that facilitates the introduction of candidates, the increase in electability is more determined by the candidate's ability to build trust, demonstrate competence, and maintain consistency in political communication. This study confirms that political branding is an effective strategy in increasing the electability of candidates with artistic backgrounds in local political contests.